Experimental and numerical investigation of forced convection heat transfer in porous lattice structures produced by selective laser melting - Ho, Jin Yao (2020)
Forced convection heat transfer in four structured porous materials produced by selective laser melting (SLM) was experimentally and numerically studied. The porous materials are lattice structures consisting of periodic arrangements of Rhombi-Octet unit cells. The lattice structures have similar porosity (ε) but are of different unit cell sizes of 5 mm, 7 mm, 10 mm and 12 mm. This investigation aims to characterize and evaluate the thermo-hydraulic properties of this new class of lattice structures. The hydrodynamic and heat transfer characteristics of the lattices structures such as the permeability (K), inertia coefficient (CE) and Nusselt number (Nu) were determined experimentally in an air flow channel in which the Reynolds number (Re) can be varied between 1300 and 7000. Using a linear heat conduction setup, the stagnant effective thermal conductivities (keff) of the various lattice structures were determined and a relationship between keff and the ligament width (d) of the lattice structure was obtained. Based on the local thermal non-equilibrium model, numerical simulations were performed to determine the interfacial heat transfer coefficients (hsf) of the lattice structures. Our results showed that the pressure drop (ΔP) and Nusselt number (Nu) of the lattice structures increase with decreasing d and the highest Nu of 906 was obtained with the L1 lattice structure which has the smallest ligament width. The lattice structures also exhibited high keff values which were up to 5.5 times higher than that of the aluminum foams. Due to the orderly arrangements of the lattice structures, their permeability-based friction factors (f⋅Da1/2) were found to be lower than the metallic foams. However, their hsf values were also lower. The Colburn j-factor and thermal efficiency index (η) of the lattice structures were determined and found to be higher than those of the commercial metallic foams and conventional pin fin heat sinks. In summary, this investigation demonstrates the promising use of a new class of lattice structures (Rhombi-Octet) for enhancing single-phase forced convection cooling.